1982
DOI: 10.1002/aja.1001650407
|View full text |Cite
|
Sign up to set email alerts
|

Development of the connective tissue network in the neonatal hamster heart

Abstract: The formation of the connective tissue network, composed principally of collagen, in the left ventricle of the neonatal hamster heart developed primarily during the first 20 days postpartum. The weave network of the endomysium, which was absent at birth, was visible by 4 days and was similar to that of the adult by 15 days postpartum. Myocyte-myocyte and myocyte-capillary struts formed gradually as the heart underwent physiological hypertrophy. These data were similar to the development of the connective tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Studies using electron microscopy, culture, and specific antigens have shown that endothelial cells produce types III, IV and V (AB 2 ) collagen as well as fibroblasts and vascular smooth muscle cells (16)(17)(18). In addition, the regular arrangement of the collagenous fibrils around the vascular perimeter is thought to be controlled by the endothelium (8,19). In light of the spatial relationship of the delicate collagen fibrils between the two BL, where there are no cellular components, it can be postulated that the endothelial cells produce fibrillar collagen to some extent and under certain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using electron microscopy, culture, and specific antigens have shown that endothelial cells produce types III, IV and V (AB 2 ) collagen as well as fibroblasts and vascular smooth muscle cells (16)(17)(18). In addition, the regular arrangement of the collagenous fibrils around the vascular perimeter is thought to be controlled by the endothelium (8,19). In light of the spatial relationship of the delicate collagen fibrils between the two BL, where there are no cellular components, it can be postulated that the endothelial cells produce fibrillar collagen to some extent and under certain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations seen in the neonatal heart include, in part, myocyte hypertrophy, increases in active and passive tension, mean arterial blood pressure, and heart rate (Zak, 1973;Hopkins et al, 1973). Also prominent among the alterations that occur during this critical period of heart development are changes in the organization and accumulation of extracellular matrix (ECM) components, particularly interstitial collagens (Borg and Caulfield, 1979;Borg, 1982).…”
mentioning
confidence: 99%
“…The connective tissue network of the vertebrate heart is composed predominantly of types I and I11 collagen fibers which form several distinct organized layers in the heart wall, similar to skeletal muscle, including the epimysium, perimysium, and endomysium (Borg and Caulfield, 1979;Borg, 1982;Borg et al, 1982Borg et al, , 1983. The endomysial layer consists of an elaborate weave network and collagen struts which connect adjacent myocytes and myocytes to capillaries.…”
mentioning
confidence: 99%
“…It is obvious that the fibroblasts (veil cells) lay down most of the collagenous and elastic components of the vascular stroma; to some extent, the endothelium as well as pericytes may also produce them (1,2,20,21). The regular arrangement of the fibrils would represent order resulting from macromolecular interactions, presumably controlled by the endothelium (14,22).…”
Section: Discussionmentioning
confidence: 99%